PERCEPTION AND INTENTION TO PARTICIPATE IN MICROTAKAFUL SCHEME AMONG INDONESIANS: AN APPLICATION OF AJZEN'S THEORY OF PLANNED BEHAVIOR - Muh Zul Hazmi Rapi; Salina Kassim (Bank Indonesia, 2023)
This study examines the intention of Indonesian Middle of Pyramid (MOP) and Botton of Pyramid (BOP) and their intention to participate in microtakaful products. The study develops an extended theory of planned behavior (TPB) model and uses structural equations modelling (SEM) to analyze data gathered from 428 respondents. Responses are obtained through a combination of online surveys and traditional paper-based distribution of questionnaires. The findings show that there is a high intention to participate in microtakaful among the respondents, with the subjective norm, price, and knowledge having positive influences on the intention to participate in microtakaful products. Meanwhile, compatibility is shown to have a positive influence on the attitude toward microtakaful, and normative belief has a positive influence on the subjective norm. However, the result shows that relative advantage has a negative influence on the attitude toward microtakaful, and attitude and price show a negative influence on the intention to participate in microtakaful products. Generally, there is a positive intention toward microtakaful among the respondents; however, knowledge and pricing are important factors that hinder the development of the microtakaful industry in Indonesia. These findings provide valuable information for the Indonesian microtakaful market and other Islamic micro institutions.